Postnatal weight increase and growth velocity of very low birthweight infants. Issue 5 (25th April 2006) - Bertino, E; Coscia, A; Mombrò, M; Boni, L; Rossetti, G; Fabris, C; Spada, E; Milani, S
Abstract : Background: Only a few studies have dealt with postnatal growth velocity of very low birthweight (VLBW) infants. Objective: To analyse weight growth kinetics of VLBW infants from birth to over 2 years of age. Patients: A total of 262 VLBW infants were selected; inaccurate estimate of gestational age, major congenital anomalies, necrotising enterocolitis, death, and loss to follow up within the first year were the exclusion criteria. Methods: Body weight was recorded daily up to 28 days or up to discontinuation of parenteral nutrition, weekly up to discharge, then at 1, 3, 6, 9, 12, 18, and 24 months of corrected age. Individual growth profiles were fitted with a seven constant, exponential-logistic function suitable for modelling weight loss and weight recovery, two peaks, and the subsequent slow decrease in growth velocity. Results: After a postnatal weight loss, all infants showed a late neonatal peak of growth velocity between the 7th and 21st weeks; most also experienced an early neonatal peak between the 2nd and 6th week. VLBW infants who were small for gestational age and those with major morbidities grew less than reference VLBW infants who were the appropriate size for gestational age without major morbidities: at 2 years of age, the difference in weight was about 860 g. The more severe growth impairment seen in VLBW infants with major morbidities is almost entirely due to the reduced height of the late neonatal peak of velocity. Conclusions: The growth model presented here should be a useful tool for evaluating to what extent different pathological conditions or nutritional and medical care protocols affect growth kinetics.